The mix of military and civilian faculty at the United States Air Force Academy : finding a sustainable balance for enduring success - Keller, Kirsten M. (Rand Corporation monograph series ;, 2013)
The mission of the United States Air Force Academy (USAFA) is "to educate, train and inspire men and women to become officers of character, motivated to lead the United States Air Force in service to our nation." To achieve this mission, USAFA provides cadets with both military training and a four-year college education similar to that offered at civilian institutions. Unlike at civilian institutions, however, USAFA academic classes are taught by a mix of active-duty military officers and civilian professors. Since civilians were formally incorporated onto the faculty at USAFA in the early 1990s, there has been continued debate over the best mix of military and civilian faculty needed to achieve the academy's mission. Furthermore, the Air Force currently faces difficulty in meeting USAFA faculty requirements for officers with advanced academic degrees, often resulting in understaffed departments. Funding for temporary faculty to fill these positions is also declining. A RAND study sought to help address these issues by examining the impact of potential changes to the current military-civilian academic faculty composition in five areas of importance to USAFA's mission and the broader U.S. Air Force: (1) cadets' officership development, (2) cadets' academic development, (3) cost, (4) staffing challenges, and (5) officer career development (i.e., how degree attainment and teaching tours at USAFA affect the career paths of active-duty military personnel at different points in their careers). Based on the study's findings, this report makes recommendations for a faculty composition that best balances these key factors and is sustainable into the future